Spatial Analysis of The Characteristics of Faculty Members at Sebha University, 2021. (Journal of Human Sciences, 2024)
The geographical distribution of educational level is considered one of the population characteristics that affect the economic and social situation, and the segment of master’s and doctorate holders represents the highest level of education in society. Therefore, this study aims to analyze the variation in the geographical distribution of faculty members at Sebha University to identification of different concentration patterns and their characteristics. The study relied on the analytical approach, based on the analysis of the questionnaire form, which represents 22% of the total faculty members at Sebha University. The study used the location quotient measure to identify models of the concentration of faculty members. The importance of the study lies in that it shows models of engagement of faculty members in the Fezzan region and the city of Sebha, and uses this to study ways to improve the status of human resources at the university. The results showed that the distribution of faculty members in the Fezzan region varied between areas of very high concentration in the municipality of Sebha, and areas of low concentration in the municipalities of Al-Shati, Murzuq, Ubari, and Ghat. The distribution of teaching staff in the city of Sebha also varied between five levels: areas of very high concentration in Hajjara, high in Mahdia, Secondary School, and Al Gourda, then moderate in the Al-Manshiya and Sokra neighborhoods, and finally low in the Al-Jadeed, Uqaid, and Nasiriyah neighborhoods, and deficient in the Abdul Kafi neighborhood. The main reasons for choosing the place of residence were that it was the original place of residence and work at the university, and then social connections. It was found that the value of economic variables for faculty members in areas of high concentration was higher compared to areas of low concentration.